Fault‐Driven Differential Exhumation in a Transpressional Tectonic Setting: A Combined Microstructural and Thermochronologic Approach From the Liquiñe‐Ofqui Fault System, Southern Andes (39°S). Issue 2 (27th January 2023) - Roquer, Tomás; Arancibia, Gloria; Seymour, Nikki M.; Veloso, Eugenio E.; Rowland, Julie; Stockli, Daniel F.; Jöns, Niels; Morata, Diego
Abstract: Crustal deformation in transpressive tectonic settings is partitioned across fault‐bounded tectonic blocks whose borders may represent ideal loci for enhanced rock exhumation. Field and petrographic analysis, geothermobarometry, zircon U‐Pb geochronology, and zircon and apatite (U‐Th)/He thermochronology were applied to intrusive and metamorphic rocks to investigate exhumation patterns of fault blocks delimited by the Liquiñe‐Ofqui Fault System (LOFS), Southern Andes (39°S). Our integrated analyses document the relative influences of magmatism, fault‐driven differential exhumation, and fault‐controlled geothermal flow along the LOFS. Magmatism was concentrated in the Early to Late Jurassic (∼182–151 Ma), Early Cretaceous (∼116–104 Ma), and Miocene (∼17–6 Ma). Dextral mylonitic deformation was most likely coeval with the Miocene pulse of magmatism. Tectonic exhumation occurred across a positive flower structure during the Late Miocene to Early Pleistocene (∼6–2 Ma), and affected kilometric‐scale tectonic blocks bound by N‐striking, steeply dipping faults of the LOFS. Fault‐controlled geothermal flow occurred from the Early Pleistocene to the present‐day (∼1.5 Ma‐present). Our results suggest that individual faults not only facilitate exhumation of tectonic blocks but also act as pathways for long‐term hydrothermal fluid flow. Key Points: Tectono‐thermal analysis reveals the timing of magmatism, mylonitization, tectonic exhumation and geothermal fluid flow Differential exhumation is controlled by N‐striking, steeply dipping faults in a positive flower structure Fault zones facilitate exhumation of tectonic blocks and continue to serve as pathways for geothermal fluid flow